Physiologically based mechanistic insight into differential risk of valproate hepatotoxicity between children and adults: A focus on ontogeny impact - Yu‐Ting Huang; Yen‐Ming Huang; Fan‐Lu Kung; Chun‐Jung Lin; Tun Jao; Yunn‐Fang Ho (CPT: Pharmacometrics & Systems Pharmacology, 2023)
Abstract The anticonvulsant valproic acid (VPA) despite complex pharmacokinetics has been in clinical use for nearly 6 decades. Previous reports indicated neonates, infants, and toddlers/preschoolers had higher risk of valproate hepatotoxicity than adults. However, dosing recommendations for those less than 10 years of age are lacking. To decipher clinical puzzles, physiologically‐based pharmacokinetic (PBPK) models of VPA and its hepatotoxic metabolite 4‐ene‐VPA were constructed and simulated with particularly integrated information of drug‐metabolizing enzyme ontogeny. Adult and pediatric PK data of VPA (n = 143 subjects) and 4‐ene‐VPA (n = 8 subjects) collected from previous reports were used for model development and validation. Sensitivity analyses were performed to characterize ontogeny impacts of CYP2C9 and UGT2B7 on dispositions of VPA and 4‐ene‐VPA across age groups. Optimal VPA dosing for each pediatric age group was also predicted and objectively judged by ensuring VPA efficacy and avoiding 4‐ene‐VPA hepatotoxicity. The study revealed UGT2B7 ontogeny was quite influential on VPA clearance even in neonates and small children. Intrinsic clearance of CYP2C9 was the most prominent determinant for areas under the concentration‐time curve of VPA and 4‐ene‐VPA in infants, and toddlers/preschoolers, reflecting higher hepatotoxicity risk due to noxious 4‐ene‐VPA accumulation in these groups. The ontogeny‐based PBPK approach complements conventional allometric methods in dosing estimation for the young by providing more mechanistic insight of the processes changing with age. The established ontogeny‐based PBPK approach for VPA therapy deserves further corroboration by real‐world therapeutic data to affirm its clinical applicability.